Research on the sustainable design strategies of vernacular architecture in Southwest Hubei-A case study of the First Granary of Xuan'en County. - Wei Xu; Qinyu Wang; Hao Deng; Zhenhua Zhu (PLoS ONE)
Vernacular architecture, optimized over centuries to create comfortable thermal environments using sustainable design strategies and local materials, can offer valuable insights for contemporary eco-friendly architectural design. This research investigates the sustainable design strategies of vernacular architecture in southwest Hubei, focusing on the First Granary of Xuan'en County as a representative case study. Through field investigations of indoor environments, this study explores how traditional architectural practices have addressed the region's complex mountainous terrain and hot, humid climate. Major sustainable design strategies include rational site selection and layout adapted to the terrain, building forms and spatial organizations tailored to the environmental conditions, and the use of a "double-skin" envelope structure to enhance thermal insulation and ventilation. The results demonstrate that the average temperature of the grain depot does not exceed 25°C without active means, meeting the quasi-low temperature storage standard. Through comprehensive field research and analysis, this study demonstrates how these traditional design strategies not only improve indoor thermal comfort and energy efficiency but also align with local economic levels and modern living requirements. By leveraging passive design techniques rooted in local cultural and environmental contexts, this research provides a framework for integrating these strategies into contemporary sustainable architecture.